Genetic transformation of wheat–Present status and future potential - Mamrutha, H M; Kumar, Rakesh; Venkatesh, Karnam; Sharma, Pradeep; Kumar, Raj; Tiwari, Vinod; Sharma, Indu (Journal of Cereal Research, 2014)
Wheat is the major staple food crop of the world immediately after rice. Since green revolution, its production has increased with the introduction of input responsive, semi dwarf, high yielding varieties. In the recent years, conventional breeding helped in sustaining the yield levels but failed to provide a signifcant yield jump. Under such circumstance genetic transformation could serve as a useful tool for transferring target gene of interest for further crop improvement. Transformation in wheat has been least successful because of low transformation effciency and genotype dependency. During last decade, tremendous efforts has been made using either biolistic particle or Agrobacterium-mediated transformation with different explant types to transfer several marker genes, biotic and abiotic stress tolerance genes into wheat. This review presents different techniques applied in wheat transformation with a view to encourage further long-term wheat improvement research by genetic engineering approaches.